Azure Arc Enabled Kubernetes for Multicloud - Buchanan, Steve (O'Reilly Media, Inc., 2021)
Getting an organization up to speed on a single cloud is a challenge, but mastering two or more cloud platforms is much more demanding. With Microsoft's Azure Arc, IT teams can deploy workloads and manage resources no matter where they exist. This report demonstrates how Azure Arc lets you extend the Azure control plane for Kubernetes across multiple clouds as well as on-premises deployments. Nine-time Microsoft MVP Steve Buchanan shows system administrators, cloud administrators, DevOps engineers, and site reliability engineers how to manage, secure, and govern Kubernetes clusters with Azure Arc. You'll discover why this multicloud platform is the ideal solution for working in today's increasingly hybrid computing world. Understand the new management challenges that multicloud brings Learn how Azure Arc drives consistent governance, security, and management across multicloud Gain valuable insights into Microsoft's Azure ARM control plane for Kubernetes Learn how Azure Arc manages Kubernetes clusters across on-premises and multiple cloud deployments Explore the GitOps technology pattern and operating model for cloud native applications and Kubernetes Use Azure Arc-enabled Kubernetes and GitOps to deploy configurations and applications to Kubernetes clusters.